Spectrum of Complications in Children with Moderate to Severe DKA Admitted in Pediatric Intensive Care Unit of a Tertiary Care Hospital - Ambreen Aslam, Nighat Sultana, Muhammad Sarwar, Anila Jamil, Fareeha Kausar, Umer Waqar, Ambreen Aslam, Nighat Sultana, Muhammad Sarwar, Anila Jamil, Fareeha Kausar, Umer Waqar (Journal of Rawalpindi Medical College, 2022)
Background: Diabetic Ketoacidosis (DKA) is the major source of mortality and morbidity in type 1 Diabetes Mellitus. Cautious fluid resuscitation, insulin and electrolyte replacement along with observation for complications is the mainstay of treatment. Early identification of complications lead to better management and outcome. Objective: To find out the complications of moderate to severe DKA in pediatric patients admitted in Pediatric Intensive Care Unit (PICU). Methods: Cross-sectional Study was conducted in PICU of University of Child Health Sciences & The Children’s Hospital, Lahore from Jan, 2015 to Dec, 2018.Data was collected from retrospective records of patients admitted in PICU. All patients with moderate/severe DKA were included. Patients with developmental delay were excluded. Data was analyzed using SPSS version 25. Chi-square test was used to find out p-value. Results: A total of 152 patients with moderate/severe DKA were included in the study, having mean age of 7.86 ± 4.06 years. Most patients 42% (n=64) were more than 10 years of age. Mean weight of the children was 19.89 ± 8.70 kg. Majority 59% (n= 89) were of new onset diabetes. Severe DKA was seen in 74% while moderate DKA in 26% patients. The complications seen were: hypokalemia 33% (n=50), cerebral edema 28% (n=42), hypernatremia 18% (n=27), hyponatremia 8% (n=12) and acute kidney injury (AKI) in 7% (n=11). Survival rate was 85% while mortality rate was 15%. Conclusion: Hypokalemia and cerebral edema were the most common complications observed. Complications were more common in those patients who presented with DKA in first presentation. Key words: complications, DKA severity, children, PICU.